2010
DOI: 10.1007/s11431-010-0128-y
|View full text |Cite
|
Sign up to set email alerts
|

Principle of equipartition of entransy dissipation for heat exchanger design

Abstract: In the present work, a principle of equipartition of entransy dissipation (EoED) for heat exchanger design is established, which says that for a heat exchanger design with given heat duty and heat transfer area, the total entransy dissipation rate reaches the minimum when the local entransy dissipation rate is uniformly distributed along the heat exchanger. When the heat transfer coefficient is unfixed, the total entransy dissipation obtained by the EoED principle is less than that obtained by the principle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Based on the concept of entransy dissipation, Guo et al [4] developed the extremum entransy dissipation principle, defined the entransy-dissipation-based thermal resistance, and proposed the minimum thermal resistance principle. It was found that the principles of the entransy theory are appropriate to the optimization of heat conduction [5][6][7][8][9][10][11][12][13], heat convection [14][15][16][17], thermal radiation, design of heat exchangers [21][22][23][24][25][26][27] and phase change heat transfer processes [28]. Eqs.…”
mentioning
confidence: 99%
“…Based on the concept of entransy dissipation, Guo et al [4] developed the extremum entransy dissipation principle, defined the entransy-dissipation-based thermal resistance, and proposed the minimum thermal resistance principle. It was found that the principles of the entransy theory are appropriate to the optimization of heat conduction [5][6][7][8][9][10][11][12][13], heat convection [14][15][16][17], thermal radiation, design of heat exchangers [21][22][23][24][25][26][27] and phase change heat transfer processes [28]. Eqs.…”
mentioning
confidence: 99%
“…Meanwhile, the temperature difference between the hot and cold fluids is uniform along the heat exchanger, which is called the principle of equipartition of heat flux (EoHF) in this paper. Guo et al [19] pointed out that the entransy dissipation rate reaches the minimum for a given heat duty and heat transfer area when the local entransy dissipation rate is uniformly distributed along the heat exchanger, no matter whether the heat transfer coefficient is constant or variable, which is called the principle of equipartition of entransy dissipation (EoED). They found that the EoED principle has better performance than the EoTD principle when heat transfer coefficient is variable.…”
mentioning
confidence: 99%
“…When the heat transfer coefficient is constant, these three principles are equivalent [19]. However, the reality is that the heat transfer coefficient is variable in heat exchangers.…”
mentioning
confidence: 99%
See 2 more Smart Citations